Representasi Perpustakaan pada Video Musik The Story of Us - Leila Karunia (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This study is a semiotic analysis of library representation in the music video of a song. The study aims to analyze the representation of the library in music videos. Data collection techniques through observation and literature study. Analysis with Ferdinand De Saussure's semiotic theory approach. The results of this study show that the representation of the library in the music video of The Story of Us is a traditional library, namely an ancient building with a European architectural style. Facilities and infrastructure such as tables, chairs, and bookshelves made of wood and thick books. There are no library facilities that use the latest technology seen. Libraries are also represented as a place for dating users. The representation of the librarian in this music video is a librarian who is depicted with rigid and unfashionable stereotypes.